Cross-Cultural Validity of the Child and Adolescent Dispositions Model in a Clinical Sample of Children With Externalizing Behavior Problems - Del Giudice, Teresa; Tervoort, Janina; Hautmann, Christopher; Walter, Daniel; Döpfner, Manfred (Frontiers in Psychology, 2020)
Background: The Child and Adolescent Dispositions Scale – parent rating (CADS-P) explores three emotional dispositions that may enlarge the probability of future externalizing problem behavior. The English version has proven its psychometric quality within a population-based sample of children and adolescents. The presents study investigates the German version of the CADS-P by examining a clinically referred sample of children with externalizing behavior problems. Methods: The sample included 132 children aged 4-11 years with a diagnosis of attention-deficit/hyperactivity disorder (ADHD) or oppositional defiant disorder (ODD). The factor structure of the CADS-P was evaluated using exploratory (EFA) and confirmatory factor analyses (CFA). Reliability was estimated using internal consistency (Cronbach’s alpha). Validity was assessed through linear regression analyses, with symptoms of externalizing (conduct disorder (CD), ODD, ADHD) and internalizing behavior problems (anxiety, depression) as criterion variables and the three CADS-P factor scores as predictors. Results: After eliminating 8 items due to insufficient psychometric properties, EFA and CFA supported a three-factor solution for the German CADS-P. Cronbach’s alpha coefficient exceeded α = .70 for all subscales. Mostly, as predicted, the CADS-P dimensions were associated with symptoms of ODD/CD and ADHD and symptoms of anxiety and depression. Conclusions: The present study provides evidence for the cross-cultural validity of the CADS-P in a non-English-Speaking country. Results show that the German version of the CADS-P is a reliable and valid parent questionnaire for assessing prosociality, negative emotionality and daring as emotional dispositions that may enlarge the probability to develop externalizing problem behavior.